A discontinuous smooth particle hydrodynamics method for modeling deformation and failure processes of fractured rocks - Chengzhi Xia (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
A discontinuous smoothed particle hydrodynamics (DSPH) method considering block contacts is originally developed to model the cracking, frictional slip and large deformation in rock masses, and is verified by theoretical, numerical and/or experimental results. In the DSPH method, cracking is realized by breaking the virtual bonds via a pseudo-spring method based on Mohr–Coulomb failure criteria. The damaged particles are instantaneously replaced by discontinuous particles and the contact bond between the original and discontinuous particles is formed to simulate the frictional slip and separation/contraction between fracture surfaces based on the block contact algorithm. The motion of rock blocks and the contact force of discontinuous particles are determined following Newton's second law. The results indicate that the DSPH method precisely captures the cracking, contact formation and complete failure across six numerical benchmark tests. This single smoothed particle hydrodynamics (SPH) framework could significantly improve computational efficiency and is potentially applicable to broad multi-physical rock engineering problems of different scales.